HLA Associations in pediatric autoimmune liver diseases: Current state and future research initiatives - Mack, Cara L. (Frontiers in Immunology, 2022)
The strongest genetic association with autoimmunity is within chromosome 6p21, where the human leukocyte antigen (HLA) complex resides. This review will focus on the HLA associations within pediatric autoimmune hepatitis, autoimmune sclerosing cholangitis and primary sclerosing cholangitis. In general, there is considerable overlap in HLA genotypes conferring susceptibility to pediatric autoimmune liver diseases, however unique HLA associations and protective HLA genotypes exist. There are numerous areas for future research initiatives in pediatric autoimmune liver diseases and HLA association with clinical outcomes, autoantigen discovery and novel therapeutics targeting the HLA- autoantigen- T cell pathway will be highlighted.